2019
DOI: 10.21203/rs.2.161/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intra-operative red blood cell transfusion and mortality after cardiac surgery

Abstract: Background Anemia in cardiac surgery patients has been associated with poor outcomes. Transfusion of red blood cells during surgery is common practice for perioperative anemia, but may come with risks. Little is known about the association between intra-operative transfusion and mortality in patients undergoing cardiac surgery. Methods Single centre historical cohort study in 2933 adult patients undergoing coronary surgery with or without aortic valve replacement from June 2011 until September 2014. To esti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A total of 35 units of pRBCs was transfused in our case, which was significantly greater compared to a previous single center study where a median eight units of pRBCs were transfused during total arch replacement surgery [7]. Increased amount of transfusion during cardiac surgery was reported to be associated with higher morbidity and mortality rate [8][9][10]. Therefore, we could not exclude the possibility that massive gastric bleeding during the surgery negatively affected our patient's postoperative outcome.…”
Section: Discussionmentioning
confidence: 76%
“…A total of 35 units of pRBCs was transfused in our case, which was significantly greater compared to a previous single center study where a median eight units of pRBCs were transfused during total arch replacement surgery [7]. Increased amount of transfusion during cardiac surgery was reported to be associated with higher morbidity and mortality rate [8][9][10]. Therefore, we could not exclude the possibility that massive gastric bleeding during the surgery negatively affected our patient's postoperative outcome.…”
Section: Discussionmentioning
confidence: 76%
“…Other groups have also reported the intraoperative PRBC transfusion was associated with operative mortality. 3,16,17 The cause of operative mortality in ATAAD repair is very complex due to the complexity of the disease. A direct cause-effect link between ABT and better early survival was difficult to establish at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown preoperative anemia is associated with significantly increased risk of renal failure, stroke, and mortality. [13][14][15][16] Vlot and colleagues found that there was a 3-fold increased risk of 30-day mortality for patients who were older, had lower preoperative hemoglobin levels, and underwent combined procedures with longer pump times. 16 There are several other studies showing that cardiac surgery patients with anemia necessitating blood transfusions have an increased risk of adverse outcomes and mortality.…”
Section: Manage Anemia and Blood Transfusionmentioning
confidence: 99%
“…[13][14][15][16] Vlot and colleagues found that there was a 3-fold increased risk of 30-day mortality for patients who were older, had lower preoperative hemoglobin levels, and underwent combined procedures with longer pump times. 16 There are several other studies showing that cardiac surgery patients with anemia necessitating blood transfusions have an increased risk of adverse outcomes and mortality. [13][14][15] Perioperative allogenic blood transfusions have, themselves, been associated with postoperative morbidity.…”
Section: Manage Anemia and Blood Transfusionmentioning
confidence: 99%
See 1 more Smart Citation